2003
DOI: 10.1128/aem.69.9.5198-5206.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil pH on the Biodegradation of Chlorpyrifos and Isolation of a Chlorpyrifos-Degrading Bacterium

Abstract: We examined the role of microorganisms in the degradation of the organophosphate insecticide chlorpyrifos in soils from the United Kingdom and Australia. The kinetics of degradation in five United Kingdom soils varying in pH from 4.7 to 8.4 suggested that dissipation of chlorpyrifos was mediated by the cometabolic activities of the soil microorganisms. Repeated application of chlorpyrifos to these soils did not result in the development of a microbial population with an enhanced ability to degrade the pesticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(194 citation statements)
references
References 30 publications
11
173
1
9
Order By: Relevance
“…Therefore degradation by these materials may be attributed to microbial degradation which may be due to utilization of pesticide as carbon source by the microorganisms (Singh et al, 2003 andSharaf et al, 2006). But studies show that pesticide cause damage to the microorganisms (Olaitan and Abiodun 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore degradation by these materials may be attributed to microbial degradation which may be due to utilization of pesticide as carbon source by the microorganisms (Singh et al, 2003 andSharaf et al, 2006). But studies show that pesticide cause damage to the microorganisms (Olaitan and Abiodun 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major environmental trepidations with pesticides is their capacity to affect soil, because of their persistence and mobility in the soil (Walker, 2003). The effects of Chlorpyrifos and quinolphos on the germination of radish and green gram seeds were tested.…”
Section: Introductionmentioning
confidence: 99%
“…(Ansaruddin and Vijayalakshmi 2003). It has been reported that repeated application of chlorpyrifos to the soil did not result in the development of a microbial population with the enhanced ability to degrade the pesticide (Singh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of chlorpyrifos degradation was low in acidic soils, but increased considerably with increasing soil pH (4.7-8.4). High pH not only helps to develop enhanced chlorpyrifos degradation, but is also required to maintain it over long periods [22]. In groundwater, the half-life of chlorpyrifos decreases from 49.9 d to 44.4 d when pH increased from 7 to 8.5 [23].…”
Section: Removal Efficiencymentioning
confidence: 99%
“…However, less than 2.5% of added chlorpyrifos is reported to mineralize in wetland microcosms [29]. The mineralization that occurs is mostly due to microbial metabolism, as chlorpyrifos is rapidly degraded and mineralized to CO 2 when the test soils are amended with enhanced microorganisms [22]. Further toxic assessments are needed to accurately determine the rate of ultimate chlorpyrifos mineralization in CWs.…”
Section: Residues In the Substratementioning
confidence: 99%